Identificación de la Vulnerabilidad Física en las áreas de recarga hídrica de mayor importancia en el piso Bioclimático bsbn04 Bosque Siempreverde Montano Bajo, en el Sector La Esperanza, Cantón Pujilí, Provincia de Cotopaxi, 2018 - Zambrano Topa, Laydi Stefania (2019)
The objective of this research work was to identify the physical vulnerability on water recharge zones, it is the greatest importance in the bioclimatic floor BsBn04, it is ubicates in La Esperanza, Pujilí. The Vulnerability was identified through three components: 1) Factors by exposure; same ones that include deforestation, agricultural aptitude, production systems, and mining cadastres. 2) Fragility factors; that contain the use of the soil, and soil texture. 3) Resilience factors; which contain protected areas and ecosystems. Thus, geographic data is going to be collected, which ones were cut and weighted according to low, medium and high values of vulnerability. The values were converted to raster images and reclassified according to their importance in each bioclimatic floor. The generation of vulnerability maps was created using map algebra, where the layers were added and divided by number of vulnerability analyzed components